2002
DOI: 10.1108/03074350210767933
|View full text |Cite
|
Sign up to set email alerts
|

The early attraction of S&P index funds: is perfect tracking performance an illusion?

Abstract: 2012),"On the dynamics of tracking indices by exchange traded funds in the presence of high volatility", Managerial Finance, Vol. 38 Iss 9 pp. 804-832 http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…These results once again demonstrate the difference in measuring the tracking errors of ETFs using daily versus monthly return figures. A fairer comparison is with the daily tracking errors employing the R-square of S&P 500 index funds documented in Cresson, Cudd, and Lipscomb (2002), which found values ranging from 0.9052 to 0.9609. However, the values of the R-square documented in this study are still substantially below those documented in the U.S. and Australia.…”
Section: Tracking Errors Of Etfsmentioning
confidence: 97%
“…These results once again demonstrate the difference in measuring the tracking errors of ETFs using daily versus monthly return figures. A fairer comparison is with the daily tracking errors employing the R-square of S&P 500 index funds documented in Cresson, Cudd, and Lipscomb (2002), which found values ranging from 0.9052 to 0.9609. However, the values of the R-square documented in this study are still substantially below those documented in the U.S. and Australia.…”
Section: Tracking Errors Of Etfsmentioning
confidence: 97%
“…Previous literature has used the following OLS regression of ETF returns on index returns as a measure of tracking performance (see Pope and Yadav, ; Cresson et al ., ; Rompotis, ): Here r p is the return on the ETF, r b is the return on the relevant index, and is the error term. The standard error of the above regression is another measure of tracking error (TE3).…”
Section: Methodsmentioning
confidence: 99%
“…Previous literature has used the following OLS regression of ETF returns on index returns as a measure of tracking performance (see Pope and Yadav, 1994;Cresson et al, 25 Edhec's recent survey of European ETF investors found that 73% of investors use TE1 as a measure of tracking performance while 44% assess the tracking performance based on correlation of the two assets and only 6% use metric based on cointegration. Other mentioned measures were simple comparison of mean returns (used by 23% investors) and asymmetric tracking error (used by 9% investors) (see Edhec, 2009).…”
Section: Tracking Error -Ols Approachmentioning
confidence: 99%
See 2 more Smart Citations